Effect of gentiopicroside on endogenous formaldehyde homocysteine–pathway related proteins in rats with non-alcoholic steatohepatitis - Chen, Jiaxin; Zuo, Huiling; Jiao, Yuhang; Zhao, Huanhuan; Ma, Xuan; Xiao, Yahui; Li, Xiangqiong; Zhao, Wei; Shi, Anhua; Chen, Wenhui (Frontiers in Pharmacology, 2026)
BackgroundNon-alcoholic steatohepatitis (NASH) is a progressive form of non-alcoholic fatty liver disease (NAFLD) characterised by high prevalence, increasing incidence among younger individuals and poor prognosis. NASH pathophysiology is not completely understood, and at present, there are no viable pharmacological treatments for this condition in clinical practice. Gentiopicroside (GPS). Can alleviate NASH by reducing inflammatory responses, inhibiting oxidative stress and influencing blood lipid levels.ObjectiveTo examine the preventive and therapeutic effects of gentiopicroside (GPS) on proteins and metabolites related to the endogenous formaldehyde-homocysteine (FA-HCY) pathway as well as on oxidative stress in NASH rats.MethodsA high-fat, high-sugar diet was used to create a NASH rat model, and the rats’ liver weight, body weight and liver index levels were measured. Oil red O and hematoxylin and eosin (HE) stainings were used to detect pathological alterations in the rat livers. Serum biochemical kits were used to identify biochemical markers in the rat serum. Markers linked to oxidative stress and metabolites associated with the endogenous FA-HCY pathway index were identified using Enzyme-linked immunosorbent assays (ELISA) kits. Gas chromatography was employed to measure the amount of endogenous FA in the liver and serum. Western blotting and real-time (RT) PCR were used to determine the relative expression levels of proteins and mRNAs associated with the endogenous FA-HCY pathway in rat liver tissues. Immunofluorescence was used to measure the relative fluorescence intensities of the proteins MTHFR, MAT1A and ALDH2.ResultsA diet rich in fats and sugars results in weight gain and considerable steatosis. GPS can mitigate hepatic steatosis in NASH rats, reduce NAFLD activity scores and decrease the oil red O-stained area. The NASH rats’ serum biochemical markers should be improved. In groups treated with GPS (low, medium and high dosages), the serum exhibited increased HDL-C levels (P < 0.05) and considerably lowered the levels of total cholesterol, TG, ALT, AST and LDL-C. According to oxidative stress indicators, GPS increased SOD, GSH, Glutathione S-transferases (GST) and CAT levels (P < 0.05) and decreased MDA and reactive oxygen species levels in the blood of NASH rats. Serum pathway indicators demonstrated that GPS also decreased the levels of SAH and HCY in the serum and endogenous FA in the livers of NASH rats (P < 0.05) while simultaneously increasing the level of SAM (P < 0.05). Compared with the model group, the medium-dose GPS treatment group exhibited elevated endogenous FA levels in the blood (P < 0.05). Protein analysis revealed a significant reduction in AHCY expression (P < 0.05) but a significant increase in ALDH2 and CBS levels (P < 0.05) in the GPS treatment groups. RT PCR results indicated that GPS decreased AHCY and related mRNA expression (P < 0.05) while enhancing the levels of MTHFR, MAT1A and ALDH2 and related mRNA expression (P < 0.05).ConclusionThe GPS has therapeutic benefits in NASH rats as it improves liver weight, body weight, liver index levels, liver steatosis and liver function. The efficacy of GPS in ameliorating NASH in rats may be associated with the modulation of the endogenous FA-HCY pathway and attenuation of oxidative stress.